The phylogeography and incidence of multi-drug resistant typhoid fever in sub-Saharan Africa - Se Eun Park; Duy Thanh Pham; Christine Boinett; Vanessa K. Wong; Gi Deok Pak; Ursula Panzner; Ligia Maria Cruz Espinoza; Vera von Kalckreuth; Justin Im; Heidi Schütt-Gerowitt; John A. Crump; Robert F. Breiman; et al. (Nature Communications, 2018)
Typhoid fever is caused by the bacterium Salmonella Typhi. Here, Park et al. analyse the genomes of 249 S. Typhi isolates from 11 sub-Saharan African countries, identifying genes and plasmids associated with antibiotic resistance and showing that multi-drug resistance is highly pervasive in sub-Saharan Africa.